Corporate Social Responsibility and Consumer Behavior: A Study from Pakistan - Safi, Adnan (Information Management and Business Review, 2013)
Pakistani consumers must be well informed that, in achieving their corporate goals, organizations now bear greater responsibility to develop healthy environment and aware society. This study aims towards assessment of the impact of Corporate Social Responsibility on Consumer Behavior in Pakistan and to analyze whether consumers reckon Organization’s CSR initiative before buying decisions of goods and services. Carroll definition of CSR was adopted here that addresses whole range of economic, legal, ethical and philanthropic responsibilities. A Survey Questionnaire in this regard was carried out and 313 responses were collected across the different corners of Pakistan that further lead to culmination of this analysis report. The analysis showed that there is significant positive correlation between all CSR components and consumer behavior. However, Pakistani consumer’s priority appeared to be different than offered by Carroll’s Classical Pyramid, where economic responsibility was considered to be the greatest priority, followed by philanthropic, legal & ethical responsibilities.